RESEARCH OF COMBAT STRESS IN MILITARY OFFICERS - Теслюк, Валентина; Ткачов, Владислав (SWorldJournal, 2024)
The article defines combat stress as a state of mental tension of servicemen in the process of their adaptation to the conditions of combat activity with the use of resource potential. It is noted that combat stress is accompanied by the action of stress